Atmospheric conditions of intense thaws in the Polish lowlands - Ewa Bednorz (Meteorologische Zeitschrift, 2012)
Synoptic conditions of daily changes in the snow cover depth by 5 cm were analyzed. Negative pressure anomalies appear over the North Atlantic and Scandinavia, which means low pressure systems moving over Europe along a northerly path. At the same time, positive pressure anomalies appear over the Mediterranean, indicating the expansion of the Azorean High. Such distribution of anomalies increases the horizontal baric gradient, which results in the intensification of the western and south western flow and stronger than usual winds from the SW quadrant. Transport of warm and humid air masses from the south-west brings about thaw-conducive conditions in central Europe: an increase in temperature and a considerable increase in the content of precipitable water, which means abundant precipitation. Different circulation types favorable for intense thawing were distinguished using the method of the hierarchical grouping. Two of them are characterized by the presence of deep and widespread cyclonal systems located north, north-west or west of the researched area. Less frequently, the decrease in the depth of snow cover occurs in the presence of the high located west over the Atlantic Ocean, which brings air masses from the north western direction. Such situations occur most frequently towards the end of winter.